The loop - Oliver, Ben (Science fiction writer) (Chicken House, an imprint of Scholastic Inc., 2020)
"Luka Kane has spent 736 days wrongfully imprisoned inside the Loop awaiting his execution. Each day is the same. Each day is torturous. But things are starting to change. Whispers of war are circulating. Strange things are happening to the prisoners. And the warden delivers a message: Luka, you have to get out ... Now Luka must decide whether breaking out of the Loop is his only way to survive, especially if there's any chance of saving the ones he loves. But the population on the outside may be far more terrifying than anything he could have imaged. And in order to save his family, he'll have to discover who is responsible for the chaos that has been inflicted upon the world."--